2016
DOI: 10.4137/cmped.s33071
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Growth of Infants Fed an Amino Acid-Based Formula

Abstract: OBJECTIVEThis study’s primary aim was to compare the growth (daily weight gain) of infants consuming a new (Test) amino acid-based formula (AAF) or a commercially available AAF (Control).METHODSHealthy infants were randomized to Test or Control from 14 to 112 days of age. Anthropometric measurements were taken at 14, 28, 56, 84, and 112 days of age. Tolerance records were completed prior to each visit. Serum albumin and plasma amino acids were ascertained in a subset of infants at 84 days of age.RESULTSA total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 15 publications
(18 reference statements)
4
23
2
Order By: Relevance
“…Based on the criteria outlined in Section 2.2.1 , the literature was reviewed to identify studies that reported the growth of healthy term infants exclusively fed either an EHF or AAF during early infancy. Seven controlled, randomized, prospective growth trials of healthy term infants fed EHFs or AAFs at similar time points during the first four months of life have been reported and are presented in Table 3 [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. All of these studies, except for one [ 20 ], reported data that could be compared at least for some variable to that reported in the other studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the criteria outlined in Section 2.2.1 , the literature was reviewed to identify studies that reported the growth of healthy term infants exclusively fed either an EHF or AAF during early infancy. Seven controlled, randomized, prospective growth trials of healthy term infants fed EHFs or AAFs at similar time points during the first four months of life have been reported and are presented in Table 3 [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. All of these studies, except for one [ 20 ], reported data that could be compared at least for some variable to that reported in the other studies.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported data for EHFs [ 14 , 15 , 16 , 17 , 18 ]; four studies reported data for AAFs [ 14 , 18 , 19 , 20 ] and the formulas are detailed in Table 1 . The protein in EHFs is extensively hydrolyzed, thus, a sizeable percent of the protein is in the form of FAAs, perhaps as high as 50% or more, with the remainder largely in the form of very short peptides.…”
Section: Methodsmentioning
confidence: 99%
“…An eHF should be considered as the first choice in all cases of CMPA, except the most severe ones, since it is cheaper than AAF and more effective at inducing tolerance. Several studies have demonstrated that hydrolyzed formulas support the normal growth of healthy term infants, also in the first months of life . The risk of having less than the recommended daily intake of calcium and vitamin D in children with CMPA has been shown to be lower if children consume a cow's milk–free infant formula …”
Section: Specialized Infant Formulasmentioning
confidence: 99%
“…Several studies have demonstrated that hydrolyzed formulas support the normal growth of healthy term infants, also in the first months of life. [54][55][56][57][58][59][60] The risk of having less than the recommended daily intake of calcium and vitamin D in children with CMPA has been shown to be lower if children consume a cow's milk-free infant formula. 61 Infant milk formulas from non-bovine animals (goat, ewe, mare, donkey, or camel) have been widely marketed as substitutes for cow's milk, but they are not nutritionally appropriate for infants' needs 50 and could cause harm, since they carry a high risk (up to 80%) of cross-reactivity.…”
Section: Extensively Hydrolyzed Cow's Milk Protein Formulas and Aminomentioning
confidence: 99%
“…Short-term tolerance to amino acid-based formulas has been established [10, 11]. Multiple trials of elemental formula that lasted from 12 to 15 weeks have shown normalized weight gain and growth parameters in infants with cow milk protein intolerance [12, 13]. A prospective, 16-week trial of 82 infants (age 0–8 months) showed adequate mineral status after consuming an amino acid-based formula (Neocate [NC]; Nutricia North America); the patients had milk protein intolerance but were otherwise healthy [14].…”
Section: Introductionmentioning
confidence: 99%